The readiness of prospective teachers based on online teaching competencies and learning activities in COVID-19 pandemic: A cluster analysis-based approach - Ismiyati, Ismiyati; Retnawati, Heri; Suranto, Suranto; Haryanto, Haryanto; Sholihah, Mar'atus; Tusyanah, Tusyanah (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
Many things should be done to prepare prospective teachers for providing qualified teachers. The COVID-19 pandemic is forcing teachers, including prospective teachers, to improve competency and online teaching activities. This quantitative research aims to map the readiness of prospective-teacher students of Office Administration (OA) Department related to online learning by measuring their teaching competencies and learning activities. These two variables are considered capable of measuring online teaching readiness. The research sample is 72 students. The data were collected using a questionnaire distributed via a Google Form and analyzed using K-Means with SPSS 24.0 software. The results showed that the number of clusters at low readiness level was 11 students (10 female and one male) or 15%, the number of clusters at moderate readiness level was 38 students (32 female and six male) or 53%, and the number of clusters at moderate level high readiness was 23 students (18 female and five male) or 32%. These findings show that the OA Department's prospective teachers still need to be provided with online teaching materials or skills, considering that only 32% of respondents have a high level of readiness for online learning. The community is the indicator that needs improvement for OA Department prospective teachers' readiness. It can be pursued by forming the latest and most trusted community.